Risk factors for mild cognitive impairment among older adults in a hospital in southern Nigeria - Amaefuna C. Anieto; Akinwumi O. Owolabi; Mojisola O. Owolabi; Anthony I. Nwajei; Mabel O. Onwuka (AOSIS, 2023)
Background: About 63% of people living with mild cognitive impairment (MCI) and dementia live in low- and middle-income countries (LMICs). Emerging evidence suggests that early risk factors for the development of MCI and dementia can be modified by public health and preventive intervention approaches. Aim: This study aimed to assess the prevalence of MCI in older adult patients and its relationship with some risk factors. Setting: The study was conducted among older adults at the Geriatric Clinic of the Family Medicine Department of a hospital in southern Nigeria. Methods: A cross-sectional study was carried out involving 160 subjects aged 65 years and above over a period of 3 months. Socio-demographic and clinical data were obtained using an interviewer-administered questionnaire. Subjects were accessed for impaired cognition using the 10-word delay recall test scale. Data were analysed using SPSS version 23. Results: There were 64 males and 96 females; male to female ratio was 1:1.5. Majority of the study population were in age range of 65-74 years. The overall prevalence of MCI was 59.4%. Respondents with tertiary education were 82% less likely to have MCI on logistic regression analysis (OR = 0.18, 95% CI = 0.465-0.719). Conclusion: Mild cognitive impairment was prevalent among older adults in this study and was found to be significantly associated with low level of education. Contribution: It is therefore recommended that screening for MCI and known risk factors should be prioritized at geriatric clinics.